The holistic approach to property market analysis - Kamarudin, Norhaya; Ismail, Maziah (2002)
This paper argues on the relevance of adopting the institutional economic approach as an alternative approach to the mainstream economic approach for understanding the operation of the property market. It points out the unique characteristics of the property market, which warrant for a different dimension for understanding property market behaviour. An evaluation of the different paradigm in property market justifies for a relevant approach to understand the property market. The paper examines how the institutional approach takes into consideration of the features of the property market it is analysis. Having identified the strength of the approach in addressing property market analysis, the paper then proposes a broad methodological framework for property market analysis.